Emma in the night [large type] - Walker, Wendy, 1967- (Thorndike Press, a part of Gale, a Cengage Company, 2017)
"One night three years ago, the Tanner sisters disappeared: fifteen-year-old Cass and seventeen-year-old Emma. Three years later, Cass returns, without her sister Emma. Her story is one of kidnapping and betrayal, of a mysterious island where the two were held. But to forensic psychiatrist Dr. Abby Winter, something doesn't add up. Looking deep within this dysfunctional family Dr. Winter uncovers a life where boundaries were violated and a narcissistic parent held sway. And where one sister's return might just be the beginning of the crime"--